Micro and macro socio-economic drivers of the digital divide in South Africa - Magida, Ayanda (LUP and African Minds, 2026)
The term ‘digital divide’ pertains to the disparity between those with access to digital technologies and those without, encompassing individuals, households and businesses. Initially viewed as a simple dichotomy, the understanding of the digital divide has since evolved into a multidimensional framework, emphasising the importance of meaningful connectivity. This involves consistent and uninterrupted internet access, access to suitable devices, sufficient data, and affordable connections. The digital divide is further categorised into three levels. The first level concerns physical access to digital infrastructure, encompassing access to computers, the internet, and mobile phones. The second level relates to the effective use of digital technologies, including digital literacy and skills. The third level pertains to using digital technologies to engage in economic, social and political activities. The study described in this chapter was conducted to investigate the micro and macro drivers of the digital divide in the context of South Africa, employing a concurrent mixed-method approach. The micro-level findings indicate that age, geographic location and population group are significant socio-economic factors driving the first level of the digital divide. Additionally, economic activity, population group and education level influence the second level of the digital divide. Qualitative interviews revealed three themes contributing to the digital divide's macro drivers, including the affordability of internet access and ICT devices, the availability of infrastructure such as fibre and network connectivity, and the impact of electricity challenges on internet stability. By utilising mixed methods, this study provides valuable insights into the micro and macro drivers of the digital divide, making important empirical and methodological contributions to this area of research.
Keywords: Digital divide; Socio-economic factors; Internet access; Internet usage; Resources appropriation theory; Digital divide levels; SDG-9: Industry, innovation and infrastructure